Analisis Implementasi Akad Pembiayaan Take Over Gadai Emas pada BSI KCP Subang Pamanukan dalam Pandangan Hukum Islam - Fadilah, Nina Nur; Khalid, Nour; Maulana, Luthfi; Fathurohman, Imron; Karyono, Karyono (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
This article aims to analyse the implementation of the gold pawn takeover financing contract at BSI KCP Subang Pamanukan from the perspective of Islamic law. Using qualitative methods to understand more deeply the phenomenon of the research focus, the research case study approach at BSI KCP Subang Pamanukan. Primary data sources come from interviews with the gold pawn BSI KCP Subang Pamanukan, secondary data comes from articles, books, scientific journals and research related to gold pawn takeover financing. Data collection techniques through interviews with gold pawn parties at BSI KCP Subang Pamanukan, observation and documentation. Data analysis techniques in the form of narrative analysis. The results showed that the implementation of debt transfer financing (take over) at BSI KCP Subang Pamanukan was in accordance and did not conflict with DSN-MUI Fatwa No. 31/DSN-MUI/VI/2002, namely in the implementation of the financing using qardh, rahn and ijarah contracts. This refers to the third alternative, and the implementation of some of these contracts is in accordance with Islamic law.